A new fistulose demosponge species from the Persian Gulf - Gutekunst, V.; Müller, A.u.; Pohl, T.; Brümmer, F.; Malik, H.; Fawzi, N.; Erpenbeck, D.; Lehnert, H. (Zootaxa, 2018)
During a scientific expedition to the Palinurus Rock, Persian Gulf, Iraq, a reef, which was discovered first in 2012, we found a new species which we tentatively assigned to Ciocalypta (Porifera, Demospongiae, Suberitida, Halichondriidae). Genetic results from different authors (Morrow & Cardenas, 2015, Redmond et al., 2013, Erpenbeck et al., 2012) suggest that several species of Ciocalypta and other species from Suberitida (e.g. several Axinyssa, Petromica, Topsentia, Cymbastela, Halichondria (Eumastia)) are indeed no Suberitida but belong to taxa yet unnamed. The species described here genetically clearly belongs to this new taxon outside Suberitida which awaits definition. Morphologically the new species clearly would be classified as Ciocalypta. Therefore the new species is described and compared to similar morphological species, some of them, as the type species, true Suberitida and true Ciocalypta, others belong to taxa still in need of a name.